Effect of action observation therapy on daily activities and motor recovery in stroke patients - Mei-Hong Zhu; Jing Wang; Xu-Dong Gu; Mei-Fang Shi; Ming Zeng; Chun-Yuan Wang; Qiao-Ying Chen; Jian-Ming Fu (Elsevier, 2015)
Objective: To evaluate the effects of action observation therapy, which is based on mirror neuron theory, on upper limb function and activities of daily living in patients with stroke. Methods: Sixty-one patients with stroke were randomly divided into two groups; those in the control group received routine rehabilitation treatment and nursing, whereas those in the experimental group additionally received eight weeks of action observation therapy for 30 min, six times per week. Patients receiving action observation therapy watched videos depicting a model performing specific motor actions typically performed in daily life before enacting the same actions themselves. All patients were assessed using the Fugl-Meyer assessment, Barthel index and the modified Ashworth scale at baseline and at eight weeks, after treatment. Results: After the eight weeks of treatment, both groups of patients exhibited significant improvement in all the measurements (all p < 0.05). Furthermore, the Fugl-Meyer assessment, Barthel index and modified Ashworth scale scores were significantly higher in the experimental group compared to the control group (all p < 0.05). Conclusion: Action observation therapy significantly improves upper extremity motor function and performance of activities of daily living, and alleviates upper limb spasticity in patients with stroke.